Index Analysis in Cathecism Istina katolicsanska (1732) by Franciscan Antun Bačić (Libellarium: journal for research in the field of information and related sciences, 2012)
The aim of the paper is to give an analytic description of the index in a controversial catechism Istina katolicsanska (1732) by Franciscan Antun Bačić, partly by using Hans Wellishes methodology applied to the analysis of indices in incunables and books printed between 16th and 18th century and also to cross-reference the mentioned index with well researched and described indices in the books from the 18th century. Also, the aim is to demonstrate that a part of Croatian authors and printers followed the trends of their contemporaries and that they implemented indices in their books because they valued them as an important information tool that makes the content of the work more accessible.In its initial part, this paper brings an overview of the index definitions as an information tool used for orientation in books from fields of dictionary, encyclopaedic and professional literature. The second part is dedicated to the analysis of the index in the above mentioned catechism. The contribution of the paper is dual – for the first time, a detailed analysis of an index that belongs to a book printed in Croatian language in the 18th century has been made, and consequently it enables a verification or rejection of conclusions made on the basis of research done on Hebrew and Latin manuscripts, as well as French and British books printed between 16th and 18th century. Taking into consideration that the analysis presented in this paper was done by using only one book, there is a possibility of conducting this type of research on a larger corpus of Croatian books. Also, conclusions made on analysis of one book, the controversial 18th century catechism, cannot be generalized.
Keywords: indexing – historical development; Croatian catechism; evolution of index; indices in Croatian books